Stability analysis for mathematical model of outer rim on avascular tumor growth - Nuttawat Sontichai (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. In this paper we study the linear stability of the outer rim on an avascular tumor growth model through the nonlinear system of ordinary differential equations, focusing on the relationship between growth, mutated and dead rate parameters on the proliferating and quiescent layers. We show that the system may have one or two equilibrium points, depending on whether the growth rate is less than or greater than the mutation rate of the cell density. Also, the results may be indicative for cancer treatment by radiotherapy.